The effects of low level laser therapy (Ga- Al- As) on myofascial pain dysfunction syndrome - Sahebjamei M; Azizi A; Jamali F; Marofi N (Tehran University of Medical Sciences, 2002)
Muscular pain is one of the most common causes for facial pain. Myofacial pain dysfunction"nsyndrome (MPDS) is one of the most important disorders of facial area that affected patients suffer from"npain, tenderness of one or more masticatory muscles and limitation of movements. Lack of specific and"neffective therapeutic method, makes it necessary to find a treatment to decrease pain. Considering the"nanalgesic and anti- inflammatory effects of low-level laser, some investigators have recommended it for"nMPDS patient's treatment. In this study, the effects of low level laser (Ga-Al-As) on MPDS patients"nreferred to dental faculty of Tehran University of Medical Sciences, were investigated. Twenty- two"nMPDS patents, with mean age 33.32 years, were treated for 4 weeks (12 visits). Clinical examinations"nwere performed in 6 stages. The results of this study showed that variables such as pain severity, cheek"npain, pain frequency and tenderness of masseter, temporal, internal and external pterygoid muscles, had a"nstatistically significant improvement at the end of treatment with low level laser (GA-A1-AS) which"nlasted for three months, (follow- up period). Results of this study showed that, low-level laser therapy"nhas a sedative effect on the pain and tenderness of masticatory muscles in MPDS. Patients and having an"naccurate and regular program to complete treatment period, has an important role in MPDS"nimprovement.